Investigating Students’ Perception of the Implementation of Differentiated Instruction - Hardiyanti Rahman; La Sunra; Muhammad Tahir (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
Differentiated Instruction is regarded as an essential approach in modern education because it allows teachers to design learning activities that align with students’ varying abilities, interests, and learning styles, resulting in a more inclusive and meaningful learning process. However, although several studies have examined its implementation, research focusing on students’ perceptions of Differentiated Instruction at the vocational high school level remains limited. This study aims to investigate students’ perceptions of the implementation of Differentiated Instruction, particularly in relation to learning achievement, collaboration, and motivation. This research employed a descriptive quantitative design involving 114 students at SMK 1 Gowa. Data were collected using a questionnaire that had been tested for validity and reliability, and were analyzed descriptively using SPSS. The findings indicate that 66.7% of students’ perceptions in the achievement aspect fall into the Very Positive category. Subsequently, 61.4% of students’ perceptions in the collaboration aspect are in the Positive category, and 60.3% of students’ perceptions in the motivation aspect also fall into the Positive category.